Chemical Composition and Antimicrobial Efficacy of Ferula persica Extracts: A Phytochemical and Bioactivity Assessment in Iraq - Dina Hameed Zaidan; Mohannad Hamid Jasim; Noora Hamid Ibrahim; Shwaq Talib Hameed (International Journal of Tropical Medicines, 2024)
The research presented in the tables focuses on analyzing the chemical content of extracts from the Ferula persica plant, a wild species in Iraq with significant medical and therapeutic importance dating back to ancient times. This study involved testing some chemical and physical properties of the alcoholic extract of the plant's aerial parts and evaluating its antimicrobial activity, specifically against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The study is divided into three main sections: analysis of chemical content, preliminary phytochemical screening, and evaluation of antimicrobial activity. The research reveals the chemical composition of ferula, showing a moderate loss upon drying (3.6% w/w), a high content of crude fiber (19.7%), and a total ash percentage of 7.80%. It also notes the presence of a small percentage of foreign organic matter (3.83% w/w) and the absence of a swelling index. The study provides insights into the phytochemical properties of the herb plant extracts using hexane and chloroform. The examination reveals the presence of various compounds, including alkaloids, carbohydrates, glycosides, saponins, steroidal nuclei, phenolic compounds, and tannins, tested using various reagents such as Mayer, Molisch, Balgit, and ferric chloride tests. The presence or absence of these compounds is indicated by a plus or minus sign, displaying a diverse phytochemical profile.The antimicrobial activity of the herb extracts was also studied. This section evaluates the biofilm inhibition ability of the F. persica extract on S. aureus and E. coli at two concentrations (50 and 100 mg/mL). The results indicate significant inhibition of biofilm formation in both bacteria, with slightly higher efficacy at a concentration of 100 mg/mL. Control readings, presented side by side, highlight the relative potency of the extracts.
Keywords: Chemical; Ferula persica; Iraq; antimicrobial; antioxidant